CUANTIZACION DEL ESPACIO-TIEMPO - L.Lawler, James H. (1999)
In this work there are seven major new concepts, including the assumption that space- time itself is quantized . Based on these new concepts is possible to derive more than forty sub concepts. They provide simple explanations, but his more detailed and precise about our universe time, compared to the hitherto obtained . Thus some phenomena that were considered - completely independent of each other , are explained in rather deep connection between them, the seven key concepts principles here are: (1 ) The concept of effect ( Lawler (1980 } ) , (2 ) a Model of Photon , ( 3) Composition Photonics of all particles , ( 4) Quantization of Space-Time in Espasons , (5) the Interdependence of Space and time, time is Change, ( 6) lndexamiento , Units or ldentification How much of Espasons and ( 7) theory of Everything (TOE ) : in the universe everything is lnterdependiente .